2005
DOI: 10.1007/s00280-005-0070-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, open-label study of gefitinib (IRESSA) in patients with locally advanced, metastatic, or relapsed renal-cell carcinoma

Abstract: Epidermal growth factor receptor (EGFR) expression has been associated with clinical outcome in some studies of renal-cell carcinoma (RCC). We investigated the efficacy and safety of gefitinib (IRESSA), an EGFR tyrosine kinase inhibitor, in RCC patients. This phase II trial recruited 28 patients with advanced, metastatic, or relapsed RCC. Patients received oral gefitinib 500 mg/day. Objective responses (ORs) were assessed every 2 months according to RECIST. Baseline tumor biopsies were analyzed immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 26 publications
(15 reference statements)
0
24
0
1
Order By: Relevance
“…A previous phase II trial showed that the combination of gefitinib and IFNa demonstrated a modest delay in disease progression in previously treated metastatic RCC with a mean PFS of 4.3 months, and a median overall survival (OS) of 11.4 months [26]. On the other hand, several phase II trials investigating gefitinib as a single agent in advanced RCC showed less promising results [27]. In one trial, treatment with single agent gefitinib did not result in any CR or PR, and 81% of patients had PD within 4 months of starting therapy [16].…”
Section: Discussionmentioning
confidence: 98%
“…A previous phase II trial showed that the combination of gefitinib and IFNa demonstrated a modest delay in disease progression in previously treated metastatic RCC with a mean PFS of 4.3 months, and a median overall survival (OS) of 11.4 months [26]. On the other hand, several phase II trials investigating gefitinib as a single agent in advanced RCC showed less promising results [27]. In one trial, treatment with single agent gefitinib did not result in any CR or PR, and 81% of patients had PD within 4 months of starting therapy [16].…”
Section: Discussionmentioning
confidence: 98%
“…44 However, immunohistochemical studies indicated high heterogeneity regarding intratumoral EGFR protein expression. 24 Since both anti-EGFR antibody and EGFR-TK inhibitor therapies have been introduced in RCC management, 11,13,16 it is mandatory to determine the diagnostic criteria for such treatments. The anti-EGFR antibody therapies require the expression of the wtEGFR with intact extracellular ligand-binding domain, while the EGFR-TK inhibitors require an active TK enzyme (autophosphorylation).…”
Section: Targeting Genes and Pathwaysmentioning
confidence: 99%
“…Der Einsatz des gegen c-KIT und die PDGF-Rezeptoren A und B gerichteten Imatinib (Glivec® [34]) sowie des gegen den EGF-Rezeptor gerichteten Gefitinib (Iressa® [17]) und Erlotinib (Tarceva®) zeigte als Monosubstanz keine klinische Wirksamkeit in initialen Studien beim NZK, sodass ein weiterer Einsatz dieser Substanzen fraglich erscheint. Lediglich Glivec® könnte aufgrund der häufigen ckit-Überexpression bei sarkomatoiden NZK eine Rolle in dieser auf die Immuntherapie nicht ansprechenden Subpopulation darstellen [8].…”
Section: "Small Molecules" Und Antikörperunclassified